PELAGIC FISH STOCK ESTIMATION BY USING THE HYDROACOUSTIC METHOD IN BENGKALIS REGENCY WATERS - Arthur Brown; Pareng Rengi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
North seawaters of Bengkalis as a part of Bengkalis waters also contributeby Malacca Straits waters. This area estimate 2.398 km 2 in width and consists ofBantan Sub district waters to Bengkalis sub districtwaters area. This area yielded9.291,9 tones per annum of fish with utilization rate of almost 90%. This researchhas been done in the area during Northwest monsoonat November 2012 toSeptember 2013 for estimated density, environment and distribution of fish whichused local People Vessel as a research vessel. Result of this research that TSdistribution in the surface layer shows that a relatively small value ofthe targetstrength ranges from-64 till -94dBand the highest frequency was atthe value-73till-76dB, which indicates that most ofthe fishare spread on this area was a smallfish .Keywords : Bengkalis, distribution, density, acoustic methods, target strength.